Acute liver failure related to inherited metabolic diseases in young children - Dias-Costa, F (2017)
INTRODUCTION: Pediatric acute liver failure (ALF) due to inherited metabolic diseases (IMD) is a rare life-threatening condition with a poor prognosis. Early intervention may be lifesaving. OBJECTIVE: To describe clinical presentation, investigation and outcomes of ALF related to IMD in young children. MATERIAL AND METHODS: Retrospective review of the medical records of children aged up to 24 months, admitted to a tertiary pediatric and neonatal Intensive Care Unit during a 27-year period, fulfilling the ALF criteria, with documented metabolic etiology. RESULTS: From 34 ALF cases, 18 were related to IMD: galactosemia (4), mitochondrial DNA depletion syndrome (MDS) (3), ornithine transcarbamilase deficiency (3), congenital defects of glycosylation (2), tyrosinemia type 1 (2), long-chain 3-hydroxyacyl-CoA dehydrogenase deficiency (1), hereditary fructose intolerance (1), classic methylmalonic aciduria (1) and citrulinemia type 1 (1). The median age was 1.3 months. At least one previous suggestive sign/symptom of IMD (vomiting, failure to thrive, hypotonia or developmental delay) was observed in 67% of the cases. The most common physical signs at admission included: hepatomegaly (72%), jaundice (67%) and encephalopathy (44%). The peak laboratorial findings were: mean international normalizad ratio 4.5, median lactate 5mmol/L, mean bilirubin 201μmol/L, median alanine aminotransferase (ALT) 137 UI/L and median ammonia 177μmol/L. One patient was submitted to liver transplant in ALF context (MSD). The mortality rate was 44%. DISCUSSION: The identification of IMD as a frequent cause of ALF allowed specific therapeutic measures and adequate family counselling. Particular clinical features and moderated ALT and bilirubin levels can lead to its suspicion.